Exploring how junior design professionals cope with and learn from value-based conflicts. Issue 3 (3rd July 2022) - van Onselen, Lenny; Valkenburg, Rianne; Snelders, Dirk
ABSTRACT: This article explores how junior design professionals cope with value-based conflicts. We interviewed 22 design professionals about past and current value-based conflicts and the coping strategies adopted. Applying a grounded theory approach, we identified 11 types of coping strategies employed by junior design professionals. Our findings allowed us to clarify the nature of the coping process and localise value-based conflicts in the process of collaborative practice. During the coping process, professionals learn how to handle value-based conflicts through emotional release, developing a broader action repertoire, and engaging in timely action. We also identified transitions between specific coping strategies as junior designers learned from past conflicts and developed as a professional.